Hermansky-Pudlak Syndrome: Identification of Novel Variants in the Genes HPS3, HPS5, and DTNBP1 (HPS-7) - Boeckelmann, Doris; Wolter, Mira; Neubauer, Katharina; Sobotta, Felix; Lenz, Antonia; Glonnegger, Hannah; Käsmann-Kellner, Barbara; Mann, Jasmin; Ehl, Stephan; Zieger, Barbara (Frontiers in Pharmacology, 2022)
Hermansky-Pudlak syndrome (HPS), a rare autosomal recessive disorder, is characterized by oculocutaneous albinism (OCA) and bleeding diathesis due to a defect regarding melanosomes and platelet delta (δ)-granule secretion. Interestingly, patients with HPS type 2 (HPS-2) or HPS type 10 (HPS-10) present additionally with an immunological defect. We report three patients (IP1, IP2, IP3) with different HPS subtypes (HPS-3, HPS-5, HPS-7) who suffer from a bleeding diathesis, however, only the patient with HPS-7 presents with an apparent OCA (IP3). Interestingly, the patient with HPS-7 reported additionally recurrent bacterial infections. Platelet aggregometry showed impaired platelet function and flow cytometry revealed a severely reduced platelet CD63 expression indicating a defect of platelet delta granule secretion in these patients. Panel sequencing identified novel genetic variants in the genes HPS3, HPS5 and DTNBP1 (HPS-7). Two compound heterozygous variants in the HPS3 gene (c.65C>G and c.1193G>A) were identified in IP1. A homozygous variant in HPS5 (c. 760G>T) was found in IP2. Two of them have concordant in silico pathogenicity prediction, one of them a predominantly prediction. In DTNBP1 a homozygous deletion of exon 6 was identified and Western analysis confirmed the absence of the encoded protein dysbindin confirming the diagnosis of HPS-7 (IP3). The patient showed a slightly reduced NK-degranulation previously documented in a more severe form in patients with HPS-2 or HPS-10. Remarkably, the phenotype in patients with HPS can vary substantially. Interestingly, the two index patients with HPS-3 and HPS-5, respectively, exhibit a milder OCA phenotype. The lack of apparent OCA features can lead to a delayed diagnosis of HPS, i.e. the patient with HPS-5 (IP2) was diagnosed at the age of 45 years. Even if the symptoms of OCA are obvious, the diagnosis of HPS can be delayed if the bleeding diathesis is not recognized as part of the disease: the patient with HPS-7 (IP3) was 60 years old at the time when HPS-7 was diagnosed. In the past some rare subtypes of HPS may have been underdiagnosed. NGS facilitates the identification of HPS types even with a mild phenotype.